Adjuvant chemotherapy for patients with stage II high-risk and III colon cancer: Hindering factors to adherence and impact on long-term survival - Jieun Kim; Ri Na Yoo; Hyeon-Min Cho; Bong-Hyeon Kye; Hyung Jin Kim (Korean Journal of Clinical Oncology, 2021)
Purpose Adjuvant chemotherapy is recommended after curative surgery in patients with colon cancer of high-risk stage II and stage III. However, a considerable number of patients cannot complete the scheduled adjuvant treatment for various reasons. This study investigates the hindering factors to the adherence to adjuvant chemotherapy and their impact on long-term survival. Methods A retrospective study was conducted for patients with colon cancer and had curative resection from 2009 to 2014. Among patients with pathologic stage II and III, stage II with low-risk features, double primary cancers, R2 resection cases were excluded. Patients were grouped into three groups: no-adjuvant therapy, adjuvant therapy for less than 3 months, and more than 3 months. Factors for withdrawal and the oncologic outcome were analyzed. Results Of 571 patients, adjuvant chemotherapy was recommended in 403. One hundred and sixteen patients (28.8%) did not receive adjuvant chemotherapy, 78 (19.4%) withdrew within 3 months, and 209 (51.9%) maintained for more than 3 months. Factors for not receiving adjuvant chemotherapy or withdrawing within 3 months were older than 70 and American Society of Anesthesiologists class 3 or higher. Main reasons for discontinuation before 3 months were chemotoxicity and patient’s refusal. The long-term oncologic outcome of the patients who received adjuvant chemotherapy for more than 3 months was significantly better than others. Conclusion No-adjuvant therapy or receiving them for lesser than 3 months is significantly affected by the patient’s performance status and social support, which coincides with a poor oncologic outcome. Social support and rehabilitation system may help to improve the survival outcome.